An ecogeographical study of the genus Hordeum (2nd edition) - Bothmer, R. von; Jacobsen, N.; Baden, C.; Jorgensen, R.B.; Linde-Laursen, I. (1995)
Hordeum L. belongs to the tribe Triticeae of the family Poaceae (Gramineae). It has generally been considered a well-defined, easily recognized and monophyletic plant group; this report comprises the study of its 32 different species.